Outsiders : why difference is the future of civil rights - Kramer, Zachary (New York, NY : Oxford University Press, 2019)
What is the future of civil rights? Like a living thing, discrimination evolves, adapting to its time. As discrimination becomes more individualized, as difference becomes more pronounced, we need a civil rights that is attuned to the way identity is performed today. 'Outsiders' is filled with stories that demand attention, stories of people whose search for identity has cast them to the margins.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 11, 2019).
Keywords: Civil rights; Equality; Politics and Government; Politics & government